COMPARISON OF SERVICE QUALITY BETWEEN RSI SITI AISYAH AND RSUD KOTA MADIUN IN MADIUN - Utomo, Muhammad Restu (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2015)
Hospital is one of medical facilities existed in order to treat patients who come to be treated regarding of their illness. However in Indonesia hospital as medical facilities are categorized into several categories as regulated by the government. Patients are then faced with choices in which hospital to be treated in. Improving and maintaining quality of medical care within hospital is important as quality of service provided by hospital may affect the economic growth of a region or even a country. The purpose if this study is to compare service quality between RSI Kota Madiun as private hospital and RSUD Kota Madiun as public hospital. SERVQUAL instrument is used to measure the comparison of service quality. Dimensions used in this research are empathy, tangible, assurance, timeliness and responsiveness. The research result indicates that there are significant differences of service quality between RSI Siti Aisyah Madiun and RSUD Kota Madiun. Results show that RSI Siti Aisyah Madiun delivered better service quality than RSUD Kota Madiun.